(untitled) (Research, Society and Development, 2022)
The study was carried out in the city of Sinop, Mato Grosso, and its objective was to analyze the social, economic and environmental changes that took place in the city, through a survey of the occupation process, the land use and the socioeconomic indicators. The procedures used were: survey of the municipality’s historical process of occupation, in the literature and on official agency websites, preparation of the land use and land cover map through the Geographical Information System, ArcGis 10.6 software and analysis of socioeconomic indicators, which were carried out through the collection of information in the Databases of IBGE (Brazilian Institute of Geography and Statistics), Seplan (Secretary of Planning and Economic Affairs), Seplag (State Department for Planning and Management), PNUD (United Nations Development Programme), Caged (General Register of Employed and Unemployed), Datasus (Department of Informatics of the Unified Health System) and Sebrae (Brazilian Micro and Small Business Support Service). The study revealed that the occupation of the municipality of Sinop followed the occupation dynamics adopted by the Federal Government from 1970 onwards, responding to governmental and private interests. In relation to land use, the municipality of Sinop went through intense processes of vegetal exploration, with the commercialization of wood, and later migrated to agriculture with the production of grains. It was also found that over the years the municipality has been standing out in different economic sectors, such as the service and commerce sector, becoming a pole in the region by offering products and services.